EFFECTIVENESS OF PHARMACOTHERAPY FOR NORMALIZATION OF THE BRAIN NATRIURETIC PEPTIDE, RENINE-ANGIOTENSINALDOSTERONE SYSTEM ACTIVATION AFTER SURGICAL REVASCULARIZATION OF MYOCARDIUM IN POSTINFARCTION CARDIOSCLEROSIS PATIENTS - S. A. Kovalev; V. Е. Malikov; V. Yu. Merzlyakov; A. A. Bulynin; A. В. Bulynin; E. A. Krasyukova; E. V. Malyutin; М. А. Arzumanyan (Кардиоваскулярная терапия и профилактика)
Aim.  The  research  on  medical  technologies   for  optimization  of complication prevention and of post-surgery management of patients with coronary heart disease  (CHD) with ejection fraction (EF) of the left ventricle (LV) <40% in surgical revascularization of the heart. Material and methods. In the controlled, randomized study of 103 CHD patients with severe systolic dysfunction of the LV, the effectiveness  of aortic  coronary  bypass  surgery  was  studied.  All  patients  underwent clinical investigations,  where  the  severity of patient’s  condition  was assessed, as the risks of surgery by EuroSCORE, severity of heart failure signs  by the  clinical condition  scale,  echocardiography, clinical and chemistry lab. Aldosterone levels were studied  with immune enzyme assay,  brain natriuretic peptide  — with immune enzyme assay,  redox potential (NAD/NADP) with the Sigma-Aldrich system, procollagen III of N-end peptide — with the test-system USCN, Statistics was done on the software Statistica 8.0.Results. The inclusion to pre-operation  preparing of patients  of a drug with positive inotropic properties  and decreasing the level of systemic inflammation syndrome, dosage of 2 ampules intravenously during 3 days before operation and with following 7-day post-surgery, in CHD patients with significant LV  dysfunction  influences  positively the  symptoms  of chronic heart failure, initiates the deremodeling of the heart — significantly decreases the end-systolic size and increases EF LV, reduces  pulmonary hypertension, significantly decreases the duration of artificial ventilation, timing of inotropic support, duration of stay in ICU. It is shown that the level of brain  natriuretic  peptide  (NT-proBNP) in plasma  does  negatively correlate  with EF LV (r=-0,69,  p<0,01)  and redox-potential  NAD/NADP (r=-0,89; p=0,0001). At the background of Adenotsin® treatment there is significant decrease of NT-proBNP level by the 7th day after operation by 55%, the level of renin decreases, of aldosterone  and procollagen type III in blood, that confirms the positive prognosis of treatment.  There are no negative events in the drug course of implication for the studied category of patients.Conclusion. The data obtained makes it to recommend  Adenotsin® for presurgery  medication and postsurgery  therapy in cardiovascular diseases.